1996
DOI: 10.1183/09031936.96.09102109
|View full text |Cite
|
Sign up to set email alerts
|

A five year follow-up of lung function among chemical workers using flow-volume and impedance measurements

Abstract: A A f fi iv ve e y ye ea ar r f fo ol ll lo ow w--u up p o of f l lu un ng g f fu un nc ct ti io on n a am mo on ng g c ch he em mi ic ca al l w wo or rk ke er rs s u us si in ng g f fl lo ow w--v vo ol lu um me e a an nd d i im mp pe ed da an nc ce e m me ea as su ur re em me en nt ts s S. Keman*, B. Willemse*, G.J. Wesseling**, E. Kusters + , P.J.A. Borm* A five year follow-up of lung function among chemical workers using flow-volume and impedance measurements. S. Keman, B. Willemse, G.J. Wesseling, E. Kust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Written informed consent was obtained from each worker after evaluation of a self-administered questionnaire on respiratory symptoms, smoking habits and additional questions concerning working history. Lung function was measured using the forced oscillation technique (FOT) and forced expiratory flow volume curves as described previously [Keman et al, 1996]. All subjects completed three impedance measurements and three flow volume curves.…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consent was obtained from each worker after evaluation of a self-administered questionnaire on respiratory symptoms, smoking habits and additional questions concerning working history. Lung function was measured using the forced oscillation technique (FOT) and forced expiratory flow volume curves as described previously [Keman et al, 1996]. All subjects completed three impedance measurements and three flow volume curves.…”
Section: Methodsmentioning
confidence: 99%
“…Lung function measurements were performed daily between 1:00 and 3:00 p.m. in weeks 1 and 6 and 3 times/week in weeks 2±5 of the observation period as described previously (Keman et al 1996).…”
Section: Lung Functionmentioning
confidence: 99%
“…Similarly, Blanc et al [1993] found that the development of respiratory symptoms following irritant exposures are greater among smoking workers with a history of asthma, and with persistent increases in airway responsiveness without other pulmonary function abnormalities. Recently Keman et al [1996] in a 5-year follow-up of lung function among chemical workers demonstrated a signi®cant decline in forced expiratory volume in the ®rst second (FEV1). This decline was correlated with age, years of employment, and smoking habit.…”
Section: Introductionmentioning
confidence: 99%